2013
DOI: 10.1002/ejoc.201300392
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Perfluoroalkyl Ket­ones by Using a Recyclable Oxoammonium Salt

Abstract: A novel dehydrogenation reaction of perfluoroalkyl ketones by the oxoammonium salt 4‐acetylamino‐2,2,6,6‐tetramethylpiperidine‐1‐oxoammonium tetrafluoroborate (4‐NHAc‐TEMPO+BF4–, Bobbitt's salt, 1) is described. The reaction proceeds under mildly basic conditions and appears to be unique to perfluoroalkyl ketones. A proposed mechanism for this unusual transformation is given. The byproduct of the reaction, 4‐acetylamino‐2,2,6,6‐tetramethyl‐1‐piperidinyloxy (1a), can easily be recovered and used to regenerate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…1‐(Nonanyl)‐2,2,2‐trifluoroethanol ( 1a ) and 1‐(β‐phenylethyl)‐2,2,2,‐trifluoroethanol ( 1q ) were also cleanly converted (entries 16 and 17, Table 2). Interestingly, the formation of enone 2n , which was previously reported as a potential by‐product of the oxidation of 1q , was not observed 22. A sterically more demanding adamantyltrifluoromethylmethanol ( 1r ) also produced the corresponding ketone in high yield (entry 18, Table 2).…”
Section: Optimization Of the Reaction Conditions For The Catalytic Aementioning
confidence: 75%
“…1‐(Nonanyl)‐2,2,2‐trifluoroethanol ( 1a ) and 1‐(β‐phenylethyl)‐2,2,2,‐trifluoroethanol ( 1q ) were also cleanly converted (entries 16 and 17, Table 2). Interestingly, the formation of enone 2n , which was previously reported as a potential by‐product of the oxidation of 1q , was not observed 22. A sterically more demanding adamantyltrifluoromethylmethanol ( 1r ) also produced the corresponding ketone in high yield (entry 18, Table 2).…”
Section: Optimization Of the Reaction Conditions For The Catalytic Aementioning
confidence: 75%
“…In 2013, Leadbeater et al reported a Bobbitt's salt-mediated dehydrogenation of perfluoroalkyl ketones via the α-aminooxygenation of perfluoroalkyl ketones. 164 In 2017, Han et al…”
Section: Scheme 17 C-h Oxidation and C-o Cleavage Of Ethersmentioning
confidence: 99%
“…A great potential of these ketones was shown for the synthesis of various organofluorine compounds, including carbo- and heterocycles . Various approaches to the synthesis of α,β-unsaturated CF 3 -ketones can be found in the literature. However, to the best of our knowledge, only a couple of works reported synthesis of α,β-diaryl-CF 3 -enones . Only four ketones of this class have been described.…”
Section: Introductionmentioning
confidence: 99%